2014
DOI: 10.4172/2155-6148.1000462
|View full text |Cite
|
Sign up to set email alerts
|

ECG Changes in the Elderly Urology Patients during Pre-Operative Assessment in Ibadan Nigeria

Abstract: Introduction: Electrocardiograph (ECG) is an important screening tool used to identify significant ECG changes that may alter perioperative management. Objective: To find out the pattern of ECG changes in the elderly urology patients during the pre-operative review in a tertiary centre. Study design and method: This was a prospective study of elderly urology patients recruited consecutively at the urology clinic during the pre anaesthetic review over a period of one year. Result: ECG recordings from 60 elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
2
2
0
Order By: Relevance
“…Patient in this study revealed that 28.46% of study participants had a history of comorbid disease and were taking medication. The two most common comorbidities observed in elderly surgical patients were hypertension (48.57%) and diabetes mellitus (29.11%), which is comparable to the Nigerian study by Awana EE, et al (12) and the Spanish study by Santos et al (24).…”
Section: Medical Of Participantssupporting
confidence: 82%
See 3 more Smart Citations
“…Patient in this study revealed that 28.46% of study participants had a history of comorbid disease and were taking medication. The two most common comorbidities observed in elderly surgical patients were hypertension (48.57%) and diabetes mellitus (29.11%), which is comparable to the Nigerian study by Awana EE, et al (12) and the Spanish study by Santos et al (24).…”
Section: Medical Of Participantssupporting
confidence: 82%
“…In terms of comorbid illnesses, our study revealed patients who have a history of comorbid disease were 3.4 times more likely to have preoperative abnormal ECG than those who do not have(AOR = .3.44 & 95%CI (1.65-7.18) other studies done in China by Yu et al (27), in Nigeria byAwana EE, et al (12). and Brazil by Gutiérrez, et al( 30)also con rmed that patients who have coexisting medical illness have a higher chance of having abnormal ECG.…”
Section: Factors Associated With Preoperative Abnormal Ecgsupporting
confidence: 50%
See 2 more Smart Citations